Sharia Compliance dalam Pelaksanaan Eksekusi Jaminan Gadai Rahn - Fatima Retno Ningrum; Adang Sonjaya; Siti Puryandani; Dian Anggraeny Rahim (Asy-Syari'ah, 2023)
Abstract: This research is a comprehensive study of the implementation of executions carried out by murtahin on rahn pawn collateral, approached from the perspective of Sharia economic law. The study was conducted using a qualitative descriptive research methodology, which allowed for a detailed exploration of the execution of Rahn guarantees from the perspective of Sharia economic law. The normative legal approach was employed, using secondary sources to collect Islamic regulations and laws that were most relevant to the research problem. The research was then analyzed using the Sharia economic law doctrine. The findings of this research provide the procedures for executing rahn as per the Constitutional Court Decision Letter Number 18 of 2019, in accordance with the principles of Islamic sharia as regulated in the DSN-MUI Fatwa Number 92 of 2014 concerning financing accompanied by rahn.Abstrak: Penelitian ini bermaksud untuk melakukan kajian terhadap pelaksanaan eksekusi yang dilakukan oleh murtahin atas jaminan gadai rahn dari sudut pandang hukum ekonomi syari’ah. Penelitian ini dilakukan dengan menggunakan jenis penelitian deskriptif kualitatif yang mengeksplorasi eksekusi jaminan rahn dalam pandangan hukum ekonomi syari’ah. Pendekatan yang digunakan adalah pendekatan hukum normatif dengan menggunakan sumber sekunder yang dikumpulkan dengan cara menginventarisir peraturan dan hukum islam yang sesuai dengan masalah penelitian. Penelitian ini kemudian dianalisis dengan menggunakan doktrin hukum ekonomi syariah. Hasil penelitian ini adalah tata cara pelaksanaan eksekusi dalam Surat Putusan Mahkamah konstitusi Nomor 18 Tahun 2019 sesuai dengan prinsip Syari’at Islam yang diatur dalam Fatwa DSN-MUI Nomor 92 Tahun 2014 tentang pembiayaan yang disertai rahn.